1981
DOI: 10.1093/sjaf/5.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Rating East Texas Stands for Southern Pine Beetle Susceptibility

Abstract: A ranking system developed in east Texas classifies the susceptibility of host stands to southern pine beetle (Dendroctonous frontalis Zimm.) into four categories. Input variables include pine basal area per acre, average tree height, and a categorical evaluation of land form. Higher-hazard stands are generally overstocked, have taller trees, and grow on wet or low-lying sites. Management strategies are recommended for the various hazard categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The photo-interpretable site/stand factors of host type, percent pine coverage, percent pine crown closure and landform that serve to distinguish high from non-high hazard grid blocks in the present analysis reflect host conditions known to characterize individual high hazard pine stands (MASON COSTER and SEARCY 1981;HICKS et al 1981). Thus, the hazard level for a given grid block appears directly correlated with the abundance of susceptible stands within the grid block, but not necessarily solely with the preponderance of a single site/stand factor such as host type or bottomland.…”
Section: :mentioning
confidence: 89%
See 1 more Smart Citation
“…The photo-interpretable site/stand factors of host type, percent pine coverage, percent pine crown closure and landform that serve to distinguish high from non-high hazard grid blocks in the present analysis reflect host conditions known to characterize individual high hazard pine stands (MASON COSTER and SEARCY 1981;HICKS et al 1981). Thus, the hazard level for a given grid block appears directly correlated with the abundance of susceptible stands within the grid block, but not necessarily solely with the preponderance of a single site/stand factor such as host type or bottomland.…”
Section: :mentioning
confidence: 89%
“…Once high hazard grid blocks are recognized from current resource photography, detailed mapping and hazard rating of individual stands within these grid blocks can be conducted, utilizing remote sensing methods described by MASON et al (1980), MASON and BRYANT (1983) or conventional ground-level approaches (KUSHMAUL et al 1979;HICKS et al 1981). In turn, these grid blocks can be targeted for accelerated timber harvesting or silvicultural treatments (BELANGER and MALAC 1980) to reduce the hazard level.…”
Section: :mentioning
confidence: 99%
“…(1983) experimentally manipulated stand conditions by thinning and stressing trees, and have shown that tree vigor and thus resistance to bark beetles can be improved. Hazard rating systems have been developed for southern pine ecosystems based on the premise that site and stand conditions affect the probability of successful southern pine beetle infestation (Ku et al 1980;LORIO and SOMMERS 1980;BELANGER et al 1981 ;MASON et al 1981 ;HICKS et al 1981).…”
Section: Reduction In Adult Reenerqencementioning
confidence: 99%